2021
DOI: 10.1155/2021/4874545
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Recognition of Hospital Image Based on Deep Learning: The Relationship between Adaptive Behavior and Family Function in Children with ADHD

Abstract: Chronic diseases are gradually becoming the main threat to human health. By designing an efficient hospital management platform to quickly identify the corresponding chronic diseases, it can effectively reduce the labor cost, improve the accuracy of disease identification, and improve treatment efficiency. ADHD is a common behavioral disorder in school-age children, and it is also one of the most common chronic health problems in this period. The internationally recognized prevalence of ADHD is 3%–9%. ADHD oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Studies on the relationship between family functioning and behavioral problems in children with AL have demonstrated that family functioning scores of children with AL are positively associated with behavioral problem scores [31]. This is consistent with previous studies, and Zhao con rmed that family functioning is an important factor in uencing behavioral problems in children with chronic diseases [32]. Sound family functioning can better convey emotions and perceptions, which is conducive to promoting positive psychological experiences and controlling undesirable behaviors, thereby reducing the occurrence of behavioral problems and ultimately helping the child to achieve a better prognostic outcome.…”
Section: Impact Of Family Functioning On Behavioral Problems In Child...supporting
confidence: 89%
“…Studies on the relationship between family functioning and behavioral problems in children with AL have demonstrated that family functioning scores of children with AL are positively associated with behavioral problem scores [31]. This is consistent with previous studies, and Zhao con rmed that family functioning is an important factor in uencing behavioral problems in children with chronic diseases [32]. Sound family functioning can better convey emotions and perceptions, which is conducive to promoting positive psychological experiences and controlling undesirable behaviors, thereby reducing the occurrence of behavioral problems and ultimately helping the child to achieve a better prognostic outcome.…”
Section: Impact Of Family Functioning On Behavioral Problems In Child...supporting
confidence: 89%
“…erefore, the ability to obtain computer vision is the rst step in implementing the machine intelligence. In recent years, computer vision has become a hot eld of research [3]. Today, with the continuous improvement and development of educational recording, broadcasting systems, and arti cial intelligence technology, intelligent video recording and broadcasting systems based on video surveillance and recognition technology are developing rapidly, by using the behavior action recognition algorithm based on video sequence images to identify and analyze the behavior action of teachers and students in the classroom scene video.…”
Section: Introductionmentioning
confidence: 99%